Imprinting Beyond the Founding Phase: How Sedimented Imprints Develop over Time - De Cuyper, Lien; Clarysse, Bart; Phillips, Nelson (Organization Science, 2020)
In this study, we build on the foundational observations of Selznick and Stinchcombe that organizations bear the lasting imprint of their founding context and explore how characteristics shaped during founding are coherently carried forward through time. To do so, we draw on an ethnography of a social venture where the entrepreneurs left soon after founding. In examining how an initial organizational imprint evolves beyond a venture’s founding phase, we focus on the actions and interactions of organizational members, the founders’ imprint, the venture’s new leadership, and the external environment. The process model we develop shows how the organizational imprint evolves as a consequence of the interplay between top-down and bottom-up forces. We first find that the initial imprint is transmitted through a bottom-up mechanism of imprint reinforcement, and second, that the venture is reimprinted after the founding period through two processes which we call imprint reforming and imprint coupling. The result of this is the formation of a sedimented imprint. Our findings further illuminate that, although the initial imprint sticks, its function and manifestation changes over time.